2015
DOI: 10.1111/jace.14038
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Electrical Conductivity of LaCr1−xCoxO3 Ceramics

Abstract: LaCr1−xCoxO3 solid‐solution ceramics (x = 0.0–0.3) were prepared by pressureless sintering of a submicrometer powder. The powder was synthesized by a modified glycine nitrate process at 800°C. The electrical conductivity of the material sintered at 1600°C was measured by AC four‐wire method from room temperature to 1200°C. While undoped (x = 0) LaCrO3 revealed semiconductivity dominated by thermally activated mobility of small polarons over a vast temperature range, substitution of Co for Cr gave rise for a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…No Ni 2p 3/2 XPS signal was observed on n‐Si/SiO x /Ni@Co. After ion milling of about 10 nm, the sample exhibits strong metallic Ni 2p 3/2 (852.4 eV) and metallic Co 2p 3/2 (778.2 eV) XPS peaks, demonstrating the conformal Co shell on Ni core (Figure S3a and S3b). Note that the XPS analysis on the shell without ion milling exhibited the existence of Co 2+ species with a binding energy of 780 eV and O 2− species with a binding energy of 529.6 eV, suggesting that the amorphous shell was composed of CoO (Figure S3b) . These evidences revealed that a naturally oxidized layer formed in the amorphous Co shell, probably due to its high activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No Ni 2p 3/2 XPS signal was observed on n‐Si/SiO x /Ni@Co. After ion milling of about 10 nm, the sample exhibits strong metallic Ni 2p 3/2 (852.4 eV) and metallic Co 2p 3/2 (778.2 eV) XPS peaks, demonstrating the conformal Co shell on Ni core (Figure S3a and S3b). Note that the XPS analysis on the shell without ion milling exhibited the existence of Co 2+ species with a binding energy of 780 eV and O 2− species with a binding energy of 529.6 eV, suggesting that the amorphous shell was composed of CoO (Figure S3b) . These evidences revealed that a naturally oxidized layer formed in the amorphous Co shell, probably due to its high activity.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S3d, after a long‐period CV scanning on n‐Si/SiO x /Ni@Co photoanode, the binding energy of the Co species moves from 780 to 780.5 eV, and meanwhile, the energy splitting between the Co 2p 1/2 and Co 2p 3/2 levels narrows from 15.7 to 15 eV, clearly demonstrating the transformation of Co 2+ to Co 3+ species ( i. e . CoOOH) ,,. This evidence indicated that, during the OER, the amorphous CoO or Co is easily oxidized to Co 3+ in CoOOH.…”
Section: Resultsmentioning
confidence: 99%
“…Electrode reactions over the surface of the oxides under atmospheric pressure exhibit high currents, revealed an increasingly of Cr 4? ions as the Co content increased which act as holes source [11]. The electrochemical oxidation corresponds to the reaction:…”
Section: Electrochemical Performancementioning
confidence: 99%
“…The critical point of this synthesis is the presence of nitrate in the combustion reaction, which in larger quantities, where the problem lies in the decomposition of nitrate anions with violent NO 2 , production which is especially observed in a large scale preparations during the evaporation of the solvent [10]. Recently, Bonet et al [11] have obtained LaCr 1-x Co x O 3 solid-solution synthesized by a modified glycine nitrate process at 800°C ceramics for the limited composition range (x = 0.0-0.3) and measured the electrical conductivity of these materials sintered at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of Cr-O bond is indicated by the absorption bands located centered at 857.76 cm -1 for the sample calcined at 600 o C and that centered at 883.27 cm -1 in the sample calcined at 700 o C, which were assigned to stretching vibration of the bond. These stretched vibrations are not coming from the pure O-Cr-O bond which is located at 783 cm -1 61,62 . The presence of this bond was also supported by the La-O-La absorption bands associated with bending vibration, located at around 617.77, 621.29, and 627.79 cm -1 for sample calcined at 600, 700, and 800 o C and a pure La-O-La stretching vibration located at 620 cm -1 63 .…”
Section: Acidity Analysismentioning
confidence: 99%